Relevance Analysis of Systems Analysis and Design Courses With System Analyst Skill Needs - Diah Rahmawati; Monita Rahayu; Ega Safitrah (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Entering the era of the industrial revolution 4.0, there is an increasing need for digital workers. However, based on available data, Indonesia's digital talent is still very lacking and there is a mismatch between the supply of labor and the needs of the industry which has led to an increase in the unemployment rate in Indonesia. This gap must be a concern of educational institutions, especially universities, to provide educational designs that are in accordance with industry needs. Systems analysis and design courses play an important role in the development of digital skills, especially for the System Analyst profession which is much needed at this time. Based on the various skills needed by the company for System Analysts, the relevance of the curriculum analysis and system design courses used in universities in Indonesia will be reviewed. This study uses content analysis methods to analyze information based on system analyst job advertisements and course lesson plans (RPS) for systems analysis and design courses. The data testing method is carried out using a correlation test which shows that there is no relationship between the analysis and system design courses with the needs of systems analyst skills in the industry today. With the Cartesian diagram, it is known that there are two skill categories that need to be prioritized for improvement in the learning plan for the system analysis and design course, namely testing (SIT and UAT) and basic programming.